Prototype of Coffee Drink Viscosity Measuring Tool Using LDR Sensor Base on Arduino - Reza, Muhammad; Daud, Muhammad; Nurfebruary, Nanda Sitti; Mardhiah, Ainal (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
Coffee is one of the leading plantation commodities which has a significant contribution to the Indonesian economy. Getting the perfect coffee taste is influenced by several factors. One of these factors is the level of viscosity of the coffee drink. To measure the viscosity level of a coffee drink, you need a tool to measure the viscosity level. So in this research, a device for detecting the viscosity of coffee drinks was designed using an Arduino and a light dependent resistor (LDR) sensor. The LDR sensor is capable of showing a precision level of 92.58% in measuring light intensity. The test was carried out in three stages, namely on coffee without sugar to find the limits of thick, thin and very thin. The test results show that if the average viscosity value is above 30.7 NTU, the coffee drink is categorized as thick, the average viscosity value of 21.1 to 30.7 NTU is categorized as thin and the average viscosity value below 21.1 NTU is categorized as very runny. Kopi merupakan salah satu komoditas unggulan perkebunan yang mempunyai kontribusi yang cukup nyata dalam perekonomian Indonesia. Untuk mendapatkan cita rasa kopi yang sempurna dipengaruhi oleh beberapa faktor. Salah satu faktor tersebut adalah tingkat kekentalan dari minuman kopi. Untuk mengukur tingkat kekentalan minuman kopi maka dibutuhkan sebuah alat pengukur tingkat kekentalan tersebut. Maka pada penelitian ini dilakukan dirancang alat pendeteksi kekentalan minuman kopi menggunakan Arduino dan sensor light dependent resistor (LDR). Sensor LDR mampu menunjukkan tingkat presisi sebesar 92,58% dalam pengukuran intensitas cahaya. Pengujian dilakukan dengan tiga tahapan yaitu pada kopi tanpa gula untuk mencari batas kental, encer, sangat encer. Hasil pengujian menunjukkan bahwa nilai rata-rata kekentalan di atas 30,7 NTU maka minuman kopi dikategorikan kental, nilai rata-rata kekentalan 21,1 sampai 30,7 NTU dikategorikan encer dan nilai rata-rata kekentalan di bawah 21,1 NTU dikategorikan sangat encer.